Meccanica An International Journal of Theoretical and Applied Mechanics AIMETA - Gambarotta, Luigi; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Meccanica, the official journal of the Italian Association of Theoretical and Applied Mechanics (AIMETA), was established in 1966 and has always published high quality research in various fields of mechanics. Initially, the journal's aim was to internationally promote the work done by Italian researchers in mechanical sciences. As of 1991, however, Meccanica has become a truly International Journal, in which the Italian contributions find their place alongside those of other nationalities. The primary focus of the journal is on the methodological framework shared by mechanical scientists when dealing with theoretical or applied problems. Further, attention is paid to those phenomenological aspects which are characteristic for the mechanical problem at hand. Papers submitted to Meccanica should be original and should adequately pay attention to the various aspects of mechanical and mathematical modelling, of solution, as well as of analysis of system behaviour. The journal addresses: fundamental and applications issues both in established areas of mechanics research as well as in emerging fields. contemporary research pertaining to areas such as general mechanics, solid and structural mechanics, fluid mechanics, and mechanics of machines. interdisciplinary fields at the border between different areas of mechanics, or between mechanics and other mathematical and engineering sciences, such as fluid-solid interaction; acoustic-structural coupling; thermomechanics; interaction of mechanics with dynamical systems, with advanced materials, with control, and with computation; electromechanics; biomechanics. Journal features: Full length papers; topical overviews with the possible character of tutorial; brief notes; discussions and comments on published papers; book reviews; international calendar of conferences.
Keywords: Mechanics; Mechanical engineering; Automotive engineering; Civil engineering; Classical Mechanics; Civil Engineering; Automotive Engineering; Mechanical Engineering